An Analytical Solution for Static Problems of Cantilever Curved Beams with Variable Cross Sections - István Ecsedi; Ákos Lengyel; Attila Baksa; Dávid Gönczi (International Journal of Engineering and Management Sciences, 2021)
This paper gives an analytical method to obtain the deformation of a cantilever curved beam. The curved beam considered has circular centre line and the thickness of the cross section in radial direction depends on the circumferential coordinate. The kinematics of the Euler-Bernoulli beam model is used to formulate of governing equations. The curved homogeneous and isotropic elastic beam is fixed at the one of the end cross section and on the other end cross section is subjected to concentrated forces and a couple. A numerical example illustrates the applications of the derived formulae.